Characterization of anode and anolyte community growth and the impact of impedance in a microbial fuel cell - Sanchez-Herrera, Diana (BMC Biotechnol, 2014)
BACKGROUND: A laboratory-scale two-chamber microbial fuel cell employing an aerated cathode with no catalyst was inoculated with mixed inoculum and acetate as the carbon source. Electrochemical impedance spectroscopy (EIS) was used to study the behavior of the MFC during initial biofilm (week 1) and maximum power density (week 20). EIS were performed on the anode chamber, biofilm (without anolyte) and anolyte (without biofilm). Nyquist plots of the EIS data were fitted with two equivalent electrical circuits to estimate the contributions of intrinsic resistances to the overall internal MFC impedance at weeks 1 and 20, respectively. RESULTS: The results showed that the system tended to increase power density from 15 ± 3 (week 1) to 100 ± 15 mW/m(2) (week 20) and current density 211 ± 7 (week 1) to 347 ± 29 mA/m(2) (week 20). The Samples were identified by pyrosequencing of the 16S rRNA gene and showed that initial inoculum (week 1) was constituted by Proteobacteria (40%), Bacteroidetes (22%) and Firmicutes (18%). At week 20, Proteobacterial species were predominant (60%) for electricity generation in the anode biofilm, being 51% Rhodopseudomonas palustris. Meanwhile on anolyte, Firmicutes phylum was predominant with Bacillus sp. This study proved that under the experimental conditions used there is an important contribution from the interaction of the biofilm and the anolyte on cell performance. Table 1 presents a summary of the specific influence of each element of the system under study. CONCLUSIONS: The results showed certain members of the bacterial electrode community increased in relative abundance from the initial inoculum. For example, Proteobacterial species are important for electricity generation in the anode biofilms and Firmicutes phylum was predominant on anolyte to transfer electron. R1 is the same in the three systems and no variation is observed over time. The biofilm makes a significant contribution to the charge transfer processes at the electrode (R2 and Cdl) and, consequently, on the performance of the anode chamber. The biofilm can act as a barrier which reduces diffusion of the anolyte towards the electrode, all the while behaving like a porous material. The anolyte and its interaction with the biofilm exert a considerable influence on diffusion processes, given that it presents the highest values for Rd which increased at week 20.